Perancangan Infrastruktur Jaringan Berbasis Aplikasi Packet Tracer dengan Metode Hot Standby Router Protocol - Suhanda, Yogasetya; Nurlaela, Lela; Dharmalau, Andy; Widjojo, Benediktus Sidhi (LPPM STT Terpadu Nurul Fikri, 2022)
The network infrastructure used byÂ PT. Quantum currently uses one communication line in its network infrastructure. So, when the line dies, work that requires an internet connection will be disrupted and detrimental to the agency, for that two communication lines are needed. The Hot Standby Router Protocol (HSRP) network configuration is a high availability network that provides alternative means on all infrastructure paths and critical servers that can be accessed anytime. This is very useful when the main line on the web is down; the second line on the web will automatically back up the communication line, so work is not interrupted. The purpose of this research is to design a Hot Standby Router Protocol (HSRP) network infrastructure based on the Cisco Packet Tracer application. A network configuration on the Router to set the path of data packets, which can divert the main path (Active Router) to the backup path (Backup Router) if there is a problem in distributing data packets to the destination router (Main Router). The test results of the network configuration test that are made run well, there is no data loss, and show the average reply speed is below 10 ms.